Preventing the preventable through effective surveillance: the case of diphtheria in a rural district of Maharashtra, India - Phalkey, Revati; Bhosale, Rajesh V.; Joshi, Abhijeet P.; Wakchoure, Sushil S.; Tambe, Muralidhar P.; Awate, Pradip; Marx, Michael (BMC public health, 2013)
Epidemic diphtheria is still poorly understood and continues to challenge both developing and developed countries. In the backdrop of poor immunization coverage, non-existent adult boosters, weak case based surveillance and persistence of multiple foci, there is a heightened risk of re-emergence of the disease in epidemic forms in India. Investigating each outbreak to understand the epidemiology of the disease and its current status in the country is therefore necessary. Dhule a predominantly tribal and rural district in Northern Maharashtra has consistently recorded low vaccination coverages alongside sporaidic cases of diphtheria over the last years.
Gesehen am 20.01.2022